2022
DOI: 10.1007/s11357-022-00556-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammatory markers in the diagnosis of vascular contributions to cognitive impairment and dementia: a systematic review and meta-analysis

Abstract: Vascular contribution to cognitive impairment and dementia (VCID) is a clinical label encompassing a wide range of cognitive disorders progressing from mild to major vascular cognitive impairment (VCI), which is also defined as vascular dementia (VaD). VaD diagnosis is mainly based on clinical and imaging findings. Earlier biomarkers are needed to identify subjects at risk to develop mild VCI and VaD. In the present meta-analysis, we comprehensively evaluated the role of inflammatory biomarkers in differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 77 publications
1
38
0
Order By: Relevance
“…In the current review, these findings were replicated in the context of possible links with neurodegeneration, with results specifically implicating CRP, IL-6 and soluble TNF-α receptor II. Of these three inflammatory markers, CRP has been associated with progression to dementia even after adjustment for confounding factors [85], while IL-6 has been specifically associated with vascular dementia [86].…”
Section: Integration Of Existing Results On Biomarkers Of Neurodegene...mentioning
confidence: 99%
“…In the current review, these findings were replicated in the context of possible links with neurodegeneration, with results specifically implicating CRP, IL-6 and soluble TNF-α receptor II. Of these three inflammatory markers, CRP has been associated with progression to dementia even after adjustment for confounding factors [85], while IL-6 has been specifically associated with vascular dementia [86].…”
Section: Integration Of Existing Results On Biomarkers Of Neurodegene...mentioning
confidence: 99%
“…Oxidative stress caused by systemic inflammation and hypoxia was considered to be one of the causes of dementia, which may be a mechanism that links cardiopulmonary pathology with neurocognitive impairment (Cheung et al, 2018). Inflammatory markers such as the levels of interleukin (IL)-6, C-reactive protein (CRP), and tumor necrosis factor-alpha (TNF-α) also have been reported to be elevated in patients with COPD (Deveci et al, 2010;Custodero et al, 2022). In addition, a study (Ranzini et al, 2020) showed patients with COPD may show cerebral perfusion alterations as a consequence of hypoxemia, which is an abnormal decrease in oxygen in the blood, and these changes could lead to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the importance to the vascular contributions to cognitive function ( Custodero et al, 2022 ; Kiss et al, 2022 ; Montagne et al, 2022 ). Acupuncture was found can alleviate cognitive function in Vascular dementia (VD), but the underlying mechanisms are still unclear ( Cao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%